Hybolites Revisited - Norris, Victor; Verrier, Cecile; Feuilloley, Marc (Recent Patents on Anti-Infective Drug Discovery, 2016)
Background: Hyperstructures are large assemblies of molecules and macromolecules that perform functions such as metabolism (including RNA and protein synthesis and degradation), transport, DNA replication, cell division, signalling and chemotaxis. Methods: Such hyperstructures might be manipulated by hybrid metabolites or hybolites made by a pairwise, covalently linked combination of the thousands of small molecules involved in metabolism and signalling. Results: Here, we review recent evidence for hyperstructures in prokaryotes and for interactions between hyperstructures as a determinant of the phenotype. We also mention extending hybolite therapy to eukaryotes, consider new designs for hybolites, and discuss relevant patents.
Keywords: cancer